The Effectivity of Giving Citronella Ark Blok to Improve the Quality of Etawah Crossbreed Goat Milk - Dzarnisa, Dzarnisa; Syahputra, Firman; Asril, Asril (Jurnal Agripet, 2025)
This study aimed to evaluate the effect of citronella ark blocks on the fat, lactose, and protein content of Etawah crossbreed goat milk. The study used five female Etawah crossbreed goats, each in their first and fifth lactation periods. A Latin Square Design (LSD) was employed, with five treatments and five replications, as follows: P0: 0% citronella block, P1: 2% of total ration, P2: 4% of total ration, P3: 6% of total ration, and P4: 8% of total ration. The parameters measured included milk fat, lactose, and protein content. The results indicated that the administration of citronella ark blocks had no significant effect (P0.05) on the milk quality of Etawah crossbreed goats. Before treatment, the milk had an average fat content of 4.16%, lactose content of 3.91%, and protein content of 4.11%. After treatment, the milk quality improved, with fat content reaching 4.9%, lactose content 4%, and protein content 4.16%. Therefore, the use of citronella ark blocks may enhance milk quality, offering significant benefits for the dairy goat farming industry.